5 Va, Laws ch. 14 sec. 2 at 61 - (:unkn) unknown (My University, 1738)
"That from and fter the passing of this act, it shall not be lawful for any person whatsoever, to hunt, shoot or kill, any bark, between the first day of December, and the last day of July, which shall be in any year; nor to hunt, shoot, or kill, any doe or fawn, between the first day of January, and the last day of September, in any year. And if any person whatsoever shall presume to hunt, shoot, or kill, or destroy, any such bucks, doe, or fawn, running wild in the woods, within the times herein before respectively limitted; or shall buy or receive the samee of any Indian, or other person; every such person so offending s?II forfeit and pay the sum of twenty shillings current money, for every buck, doe, or fawn, so killed, bought, or received;"
Keywords: HUNTING REGULATION